What Demotivates Foreign EFL Teachers? A Case Study in Turkish Context - Han, Turgay; Mahzoun, Zinat (Qualitative report, 2017)
This article is the report of a qualitative case study proposed to investigate the demotivation factors of foreign EFL teachers in Turkish context. To that end, two foreign teachers of English language were chosen as the subjects at a primary/ secondary school in east of Turkey. Face-to-face interviews, profile forms, field notes and diaries were used to obtain the necessary data for the research. The findings indicated that lack of effective communication with school administration and colleagues and lack of interest, attention and respect from behalf of students were the main causes of demotivation at work for both teachers.